Predictors of intracranial hemorrhage in acute ischemic stroke after endovascular thrombectomy - Enomoto, Masaya (Interv Neuroradiol, 2020)
BACKGROUND: Limited data are available regarding the predictors, clinical relevance, and bleeding rate by surgical devices of intracranial hemorrhage after endovascular thrombectomy. This is partially explained by the difference in the classification and definition of hemorrhage among studies. The purpose of this study was to identify the predictors of hemorrhagic transformation and isolated subarachnoid hemorrhage after endovascular thrombectomy. METHODS: This was a retrospective, multicenter observational cohort study of consecutive patients who underwent endovascular thrombectomy between January 2015 and December 2018. Univariate and logistic regression analyses were performed to determine the predictors, the impact on clinical outcomes, and the bleeding rate by surgical devices of hemorrhagic transformation and isolated subarachnoid hemorrhage. RESULTS: Among 610 eligible patients, hemorrhagic transformations occurred in 93 (15.2%). Fourteen patients (2.3%) were classified as having symptomatic intracranial hemorrhage. Isolated subarachnoid hemorrhage was found in 60 (9.8%) patients. In the logistic regression analyses, diabetes mellitus (odds ratio: 1.92; 95% confidence interval: 1.06–3.49) was associated with hemorrhagic transformation, and the number of device passes (odds ratio: 1.33; 95% confidence interval: 1.11–1.59) was associated with isolated subarachnoid hemorrhage. Both hemorrhagic transformation and isolated subarachnoid hemorrhage were associated with poor 90-day functional outcomes. There was a significant correlation between treatment with stent retrievers and isolated subarachnoid hemorrhage. CONCLUSIONS: Patients with diabetes mellitus were vulnerable to hemorrhagic transformation, whereas those who underwent several attempts of thrombectomy were susceptible to isolated subarachnoid hemorrhage. Both hemorrhage types worsened the functional outcome. Treatment with the stent retriever was significantly associated with postprocedural isolated subarachnoid hemorrhage.